2021
DOI: 10.31234/osf.io/zxdva
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

I remember it now, so I'll remember it later: Working Memory Representations Guide Inaccurate Predictions of Future Memory Performance

Abstract: Making accurate predictions of future memory performance (Judgements of Learning; JOLs) is a prerequisite for efficient learning. Since decades, those JOLs are assumed to be made inferentially, based on cues. This cue-utilization approach substituted the idea that JOLs are directly linked to memory quality. We criticize the reasons for the rejection of this memory-strength hypothesis because they ignore the existence of two different memory systems: working memory which holds representations immediately access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Evidence for that prediction so far is mixed: some studies showed that increasing WM load translated into weaker LTM for the same material (Forsberg et al, 2020;Fukuda & Vogel, 2019). Others found no effect of increasing WM load on LTM performance (Bartsch et al, 2019;Krasnoff & Souza, 2021). With Experiment 3 we add to the latter part of the literaturehere WM load at encoding did not affect delayed memory.…”
Section: Wm Load At Encoding Does Not Affect Delayed Memorymentioning
confidence: 90%
See 1 more Smart Citation
“…Evidence for that prediction so far is mixed: some studies showed that increasing WM load translated into weaker LTM for the same material (Forsberg et al, 2020;Fukuda & Vogel, 2019). Others found no effect of increasing WM load on LTM performance (Bartsch et al, 2019;Krasnoff & Souza, 2021). With Experiment 3 we add to the latter part of the literaturehere WM load at encoding did not affect delayed memory.…”
Section: Wm Load At Encoding Does Not Affect Delayed Memorymentioning
confidence: 90%
“…There are potentially importantyet not systematicdifferences between these studies, including the mode of presentation (simultaneous vs. sequential), the domain of memory material (visual vs. verbal); and the memory demand of the test: Bartsch et al (2019) tested memory for relations between words; Krasnoff and Souza (2021) tested continuous reproduction of color-object conjunctions, and both studies tested all word pairs in the WM test. Fukuda and Vogel (2019) as well as Forsberg et al (2020) tested item recognition, and only tested a single item in each WM trial.…”
Section: Wm Load At Encoding Does Not Affect Delayed Memorymentioning
confidence: 99%